Disparities in primary cardiovascular risks and social determinants: multilevel analysis of national surveys - Yihun Mulugeta Alemu; Nasser Bagheri; Kinley Wangdi; Alice Richardson; Dan Chateau (Critical Public Health)
Inequalities in social determinants hinder effective CVD risk prevention. Therefore, this study aimed to quantify ten-year CVD risk in Brunei Darussalam and Iraq and identify associated individual- and community-level factors to improve targeted prevention efforts. Data were from the WHO STEPS national surveys, including 971 participants from Brunei Darussalam and 1,715 from Iraq, aged 40–69. The ten-year CVD risk was calculated using the WHO-2019 laboratory-based equation, and multilevel regression models identified associated factors. The expected ten-year CVD incidence rate (fatal or nonfatal) is 136 per 1,000 individuals in Iraq and 57 per 1,000 in Brunei Darussalam. Higher CVD risk was observed among males (Iraq: β [Beta coefficient percent] = 4.56, 95%CI [3.45–5.67], p < 0.001; Brunei Darussalam: β = 3.92, 95%CI [3.46–4.37], p < 0.001), widowed, divorced, or separated individuals (Iraq: β = 7.66, 95%CI [6.35–8.97], p < 0.001; Brunei Darussalam: β = 0.95, 95%CI [0.15–1.75], p < 0.05), those with less than primary/primary education (Iraq: β = 2.61, 95%CI [0.90–4.32], p < 0.01; Brunei Darussalam: β = 2.62, 95%CI [1.91–3.32], p < 0.001), retired/unable to work individuals (Iraq: β = 11.28, 95%CI [9.87–12.68], p < 0.001; Brunei Darussalam: β = 3.24, 95%CI [2.70–3.77], p < 0.001), and those with low physical activity (Iraq: β = 3.00, 95%CI [1.60–4.40], p < 0.001). Targeted CVD prevention efforts are needed for individuals who are widowed, divorced, or separated, have lower educational attainment, are retired or unable to work, or engage in low levels of physical activity.